Toxicity Test of Ethanol Extract Lempuyang Gajah (Zingiber Zerumbet (L.) Roscoe Ex Sm.) on Bilirubin and Alkaline Phosphatase Levels in Mice (Mus Musculus): Uji Toksisitas Ekstrak Etanol Lempuyang Gajah (Zingiber zerumbet (L.) Roscoe ex Sm.) Terhadap Kadar Bilirubin dan Alkalin Fosfatase pada Mencit (Mus musculus) - Fatmawati, Ririn; Rohmah, Jamilatur (Universitas Muhammadiyah Sidoarjo, 2022)
The lempuyang gajah plant (Zingiber zerumbet (L.) Roscoe ex Sm.) is a plant that is widely used as a treatment for desease. The purpose of this study was to determine the toxic effect of the ethanol extract of lempuyang gajah (Zingiber zerumbet (L.) Roscoe ex Sm.) on levels of bilirubin and alkaline phosphatase (ALP) in the liver of mice (Mus musculus). The type of research used is descriptive quantitative with laboratory experimental methods. The mice were divided into 5 groups including normal control, negative control, dose of 4000 kg-1, 5000 kg-1 and 6000 kg-1. then observed the toxic symptoms, macroscopic, levels of bilirubin and alkaline phosphatase. The results of the phytochemical test showed that there were compounds of alkaloids, flavonoids, saponins, phenolics, steroids, triterpenoids and tannins. The results of macroscopic observations showed that the liver was still in a normal condition. The results of the One Way Anova test on bilirubin and alkaline phosphatase levels did not show any significant effect (p>0,05) influence between the normal control group, negative control, doses of 4000 kg-1, 5000 kg-1 and 6000 kg-1, so it can be said that all experimental animals had the same condition.